Strengthening Quranic Literacy as an Effort to Nurture a Generation of Strong Believers at SMK Muhammadiyah 5 Surakarta - Muh. Nur Rochim Maksum Maksum; Hanif Sunni Gunawan Hanif; Aboubacar Barry Abu; Febri Bekti Pangestu; Mufidatul Azizah; Dini Zakia Zahra (Abdi Psikonomi, 2026)
Abstract This study aims to explore the enhancement of Qur’anic literacy as an effort to nurture the Al-Mu’min Al-Qowiy generation at SMK Muhammadiyah 5 Surakarta. The Qur’anic literacy program implemented at this school focuses not only on reading and memorization skills but also on a deep understanding of the meanings of Qur’anic verses and their application in daily life. The method used in this study is descriptive qualitative, employing data collection techniques such as interviews, observations, and documentation. The results of the study indicate that the Quran literacy program has a positive impact on students’ understanding of the Quran and the development of their character. Students participating in this program demonstrated improvements in discipline, social responsibility, and mutual respect. Additionally, they were more active in religious activities outside of school and better able to manage stress and personal challenges. These findings align with the theory of religion-based character education, which states that Qur’anic literacy can serve as an effective tool in shaping students’ character. However, this study also identified several challenges, such as time constraints within the vocational high school curriculum which is more focused on technical skills that need to be addressed through a more flexible approach. Overall, this study reveals that strengthening Quranic literacy can serve as a model for the development of religion-based character education in vocational high schools in Indonesia. Keywords: Quranic Literacy, Character Education, Al-Mu’min Al-Qowiy Generation, Muhammadiyah Vocational High School, Character Formation